Penggunaan elektrod filem nipis emas dalam analisis enzim secara konduktometri - Engku Norbaya Engku Muda,; Burhanuddin Yeop Majlis,; Mohd Aman Abu Bakar, (1997)
A characterization study of thin film gold electrode was performed. The electrode was fabricated using d. c. sputtering technique and analysis was conducted by dip-in method. A microliter plate well was used as the cell for this system. Test was done at room temperature where the exact temperature was entered manually and corrected by conductivity meter (WTW model 539) at a reference temperature of 25°C. The electrode has a good reproducible characteristic (p < 0.05) with response time of one minute and recovery time of one to three minutes. Its application as an analytical tool was shown in determination of Michaelis constants in enzyme kinetic study. Urease was chosen as a model enzyme and urea was used as a substrate. Km value obtained was 3.46 mM and Vmax was 1.930 μScm-1/min